PENGARUH PERENDAMAN EKSTRAK DAUN CENGKEH (Syzygium aromaticum) TERHADAP DAYA TETAS TELUR IKAN PERES (Osteochilus kappeni) - Khaiyyum Ihza Azizi (Fakultas Pertanian Universitas Samudra, 2021)
Peres fish (Ostechilus kappeni) is a species of freshwater fish originating from the waters of Lake Laut Tawar and is classified as a freshwater commodity that has the potential to be developed in Central Aceh Regency. Squeezed fish is an endemic pelagic fish. This study aims to determine the mixture of clove leaf extract (Syzygium aromaticum) on the hatchability of pressed fish (Osteochilus kappeni) eggs. The method used was a completely randomized design (CRD) with 4 treatments and 3 replications, namely P0 (control), P1 (given a mixture of 5 ml), P2 (given a mixture of 7 ml) and P3 (given a mixture of 9 ml). Each treatment using squid eggs amounted to 30 grains. Parameters observed during the study were water quality, hatching rate (HR), larval abnormalities, survival, and water quality. The results of observations based on analysis of variance showed that the treatment given clove leaf extract to the eggs of peres fish. Significant effect (P<0.05) on egg hatchability and survival but no significant effect on larval abnormalities. The best treatment of giving clove leaf extract to peres fish eggs was in the P3 treatment (9 ml mixture).